Ethical implications of developing RNA-based therapies for cardiovascular disorders - Hostiuc, Mihaela; Scafa, Alexandru; Iancu, Bogdan; Iancu, Daniela; Isailă, Oana-Maria; Ion, Oana Mihaela; Stroe, Ana; Diaconu, Camelia; Epistatu, Dragos; Hostiuc, Sorin (Frontiers in Bioengineering and Biotechnology, 2024)
The awareness concerning RNA-based therapies was boosted significantly after the successful development of COVID-19 vaccines. However, they can potentially lead to significant advances in other areas of medicine, such as oncology or chronic diseases. In recent years, there has been an exponential increase in the number of RNA-based therapies that were evaluated as potential treatments for cardiovascular disorders. One of the areas that was not explicitly assessed about these therapies is represented by their overall ethical framework. Some studies evaluate ethical issues of RNA-based treatments in general or targeting specific disorders (especially neurodegenerative) or interventions for developing RNA-based vaccines. Much less information is available regarding the ethical issues associated with developing these therapeutic strategies for cardiovascular disorders, which is the main aim of this study. We will focus our analysis on three main topics: risk-benefit analysis (including the management of public awareness about these technologies), and justice (in both research and clinical medicine).